Meningkatkan Kemampuan Mengenal Warna Bagi Anak Tunagrahita Ringan Melalui Permainan Edukatif Puzzle di SLB Negeri 1 Padang - Gusni Rahma Yani; Asep Ahmad Sopandi (Program Studi PGMI, IAI Al-Falah As-Sunniyyah Kencong, 2020)
This study aims to determine the ability of children to recognize color to mild retarded children at SLB Negeri 1 Padang because children still have difficulty on recognizing colors. This research tries to find out whether the educational puzzle game is effective to improve the ability to recognize color in mild retarded children or not. The type of research method uses single subject research using A-B-A design. The test uses an action test that asks children to name, show and match the colors (red, yellow, green and blue). After analyzing data, the results obtained at baseline A1, children’s ability to recognize colors increases slowly. Furthermore, the condition B of the child is given a color recognition treatment using an educational puzzle game, in this condition the child’s ability to recognize color increases significantly. After that, in the A2 baseline, observations were made after treatment was given through an educational puzzle game, the child’s ability to recognize colors in this condition was good. From these results, educative puzzle games can improve children’s ability to recognize colors.